2004
DOI: 10.1002/hrdq.1094
|View full text |Cite
|
Sign up to set email alerts
|

Black and white women managers: Access to opportunity

Abstract: This study explores the differing views of Black and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…However, all the doctors I interviewed experienced forms of marginalisation and exclusion at their workplace that were particularly articulated in relation to the role of informal networks in determining the possibility of career progression within the organisation. Research has shown that informal networks are central in the reproduction and maintenance of inequalities within organisations, including opportunities for career advancement, power and influence and the identification of career possibilities in the labour market (Combs, 2003;Hite, 2004). Similar to the existing research, the employees with whom I spoke also identified informal networks as central to the organisational selection processes.…”
Section: Women and Migrant Medical Professionalssupporting
confidence: 63%
“…However, all the doctors I interviewed experienced forms of marginalisation and exclusion at their workplace that were particularly articulated in relation to the role of informal networks in determining the possibility of career progression within the organisation. Research has shown that informal networks are central in the reproduction and maintenance of inequalities within organisations, including opportunities for career advancement, power and influence and the identification of career possibilities in the labour market (Combs, 2003;Hite, 2004). Similar to the existing research, the employees with whom I spoke also identified informal networks as central to the organisational selection processes.…”
Section: Women and Migrant Medical Professionalssupporting
confidence: 63%
“…If so, HRD practitioners might focus development efforts on female EMT-paramedics to help them achieve objective career success. Also, issues related to the "double marginalization" of minority female EMT-paramedics could be explored (for example, Hite, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…They also received lower performance ratings and were less satisfied with their careers than whites were. 1980-1989 1990-1999 2000-2006 Studies by Greenhaus, Parasuraman, and Wormley (1990) and Hite (2004) challenged the appropriateness of using gender research on career success to inform understandings of the impact of race on employees' experiences of career success. Hite (2004), based on her study of the views of black and white managerial women across the United States, challenges the use of research on gender to inform career development initiatives for black women.…”
Section: What Has Been Studiedmentioning
confidence: 96%
“…1980-1989 1990-1999 2000-2006 Studies by Greenhaus, Parasuraman, and Wormley (1990) and Hite (2004) challenged the appropriateness of using gender research on career success to inform understandings of the impact of race on employees' experiences of career success. Hite (2004), based on her study of the views of black and white managerial women across the United States, challenges the use of research on gender to inform career development initiatives for black women. Consistently, significant differences exist between blacks and whites regarding perceptions of career opportunities (including promotions, choice assignments, and mentoring), with whites perceiving both blacks and whites as having the same career opportunities but blacks perceiving themselves as having fewer.…”
Section: What Has Been Studiedmentioning
confidence: 96%